Epicardial adipose tissue, cardiovascular hemodynamics and metabolic profile in heart failure with preserved and reduced ejection fraction. (14th October 2021) - Pugliese, N.R; Mazzola, M; De Biase, N; Paneni, F; Del Punta, L; Gargani, L; Mengozzi, A; Virdis, A; Nesti, L; Taddei, S; Flammer, A; Borlaug, B.A; et al.
Abstract: Background: Epicardial adipose tissue (EAT) acts as a paracrine organ and could exert direct mechanical compression on the myocardium. Purpose: We investigated the impact of echocardiographic EAT thickness on metabolic profile and cardiovascular hemodynamics at rest and during exercise in heart failure (HF) patients with reduced (HFrEF) and preserved (HFpEF) ejection fraction Methods: We prospectively enrolled 393 consecutive HF outpatients (205 HFrEF, 188 HFpEF) referred to the our hospital due to dyspnoea and/or effort intolerance. We performed a resting clinical and biohumoral evaluation, followed by combined cardiopulmonary-echocardiography exercise stress. The protocol also included 44 healthy controls. Results: Patients with HFpEF displayed the greatest EAT thickness (median 8 mm, interquartile range [IQR] 4–12 mm), while those with HFrEF had thinner EAT (median 3 mm, IQR 2–6 mm) than controls (median 5 mm, IQR 3–7 mm; p<0.0001). In HFrEF, EAT thickness was inversely associated with natriuretic peptides, Troponin T, and C-reactive protein levels. In HFpEF, it was directly correlated with Troponin-T and C-reactive protein levels. EAT thickness was inversely correlated with peak oxygen consumption (VO2) and peripheral oxygen extraction (AVO2diff) in HFpEF, while a direct association was observed in HFrEF (Fig 1). EAT resulted in an independent predictor of peak VO2 and AVO2diff in HFrEF and HFpEF regardless of body mass index, but the relationships were direct in HFrEF (standard regression coefficient [SRC] for peak VO2: 0.18, p=0.02; SRC for peak AVO2diff: 0.17, p=0.03) and indirect in HFpEF (SRC for peak VO2: −0.33, p<0.0001; SRC for peak AVO2diff: −0.25, p<0.0001). The analysis of cardiac mechanics revealed that thinner EAT was associated with worse left ventricle systolic dysfunction (average S') and remodeling (3D left ventricle mass) in HFrEF. In HFpEF, increased EAT was related to more severe left atrio-ventricular (left atrium reservoir strain/left ventricle global longitudinal strain) and right ventriculo-arterial (tricuspid annular plane systolic excursion/systolic pulmonary artery pressure) coupling (Figure 2). Conclusion: In HFpEF, EAT accumulation is associated with worse hemodynamic and metabolic profile. In HFrEF, conversely, EAT thinning portends more severe LV dysfunction and impaired global functional capacity. Funding Acknowledgement: Type of funding sources: None.